Analytica-EBC – Precision values of wort analyses: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Hagen, W.; Schwarz, H. (BrewingScience, 2000)
In Analytica-EBC (1) method 8.3: Specific Gravity of Wort by Density Meter, method 8.4: Viscosity of Wort: Glass Capillary Viscometer (IM), method 8.5: Colour of Wort: Spectrophotometric Method (IM), method 8.7: Fermentable Carbohydrates in Wort by HPLC (IM), method 8.8: Bitterness of Wort (IM), method 8.9.1: Total Nitrogen in Wort: Kjeldahl Method and method 8.11: Zinc in Wort by Atomic Absorption Spectrophotometry (IM) are described, but repeatability (r95) and reproducibility (R95) values are missing. So these methods have been collaboratively tested by members of the Analysis Committee of the European Brewery Convention in 1999 to obtain the corresponding precision data. In method 8.12: Total Polyphenols in Wort by Spectrophotometry the precision values are missing as well, but because of testing a new ammonium ferric citrate reagent the data have been postponed. The worts analyzed had extract contents of ca 18°P (% m/m), 14°P, 12°P, 10°P and 8°P respectively. The preciosion values are listed below.